2018
DOI: 10.4103/ijmm.ijmm_18_19
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Resistance in Helicobacter pylori: A Mutational Analysis from a Tertiary Care Hospital in Kashmir, India

Abstract: Tetracycline and quinolones could be the antibiotics of choice in the eradication of H. pylori in this region, while recurrence of the infection with H. pylori could be expected among patients receiving either metronidazole or clarithromycin, for eradication therapy. DST should be done on a routine basis utilising both phenotypic and genotypic methods to prevent further emergence of resistance in this region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 34 publications
2
26
0
1
Order By: Relevance
“…To our knowledge, this is the first study to examine the prevalence of antimicrobial resistance of H. pylori in Karnataka state of South India. In India, the prevalence of metronidazole-resistant H. pylori is remarkably high, with resistance rates reaching at least 80% in several areas [1618, 20, 21]. Importantly, such high occurrence of metronidazole resistance was also observed in our isolated clinical strains, indicating that conventional triple therapy consisting of metronidazole should not be used to treat H. pylori infection in Karnataka.…”
Section: Discussionmentioning
confidence: 75%
“…To our knowledge, this is the first study to examine the prevalence of antimicrobial resistance of H. pylori in Karnataka state of South India. In India, the prevalence of metronidazole-resistant H. pylori is remarkably high, with resistance rates reaching at least 80% in several areas [1618, 20, 21]. Importantly, such high occurrence of metronidazole resistance was also observed in our isolated clinical strains, indicating that conventional triple therapy consisting of metronidazole should not be used to treat H. pylori infection in Karnataka.…”
Section: Discussionmentioning
confidence: 75%
“…29 All the ureC positive cases were either RUT or histological staining positive. 42,43 Prevalence of the particular point mutations varies across geographical areas. On the contrary, Gehlot et al (2016) and Nakamura et al (2007) reported 87.5% and 99.0% point mutation at A2143G position.…”
Section: Resultsmentioning
confidence: 99%
“…Since macrolide antibiotics show cross resistance, the higher clarithromycin resistance rates could be attributed to indiscriminate use of erythromycin and azithromycin in our population for respiratory infections [ 33 ]. Antibiotic resistance is an important conditioning factor for the success of H. pylori treatment.…”
Section: Main Textmentioning
confidence: 99%